INVESTIGATING NON-ENGLISH DEPARTMENT STUDENTS’ MOTIVATION IN EFL WRITING - Lathif, Masyhudi (International Journal of Indonesian Education and Teaching (IJIET), 2017)
This research explores students’ voices towards motivation in English writing. It particularly scrutinizes the factors influencing students’ motivation in the teaching and learning process of writing. The participants of this study were 20 non-English department students enrolled in English IV subject which was a general English course offered by Language Training Centre of Muhammadiyah University of Yogyakarta. The data were collected through a questionnaire with open-ended questions in which the participants were asked to write their opinion and reflection with regard to the issue. The results of this study revealed that there were six factors fostering learners’ motivation in EFL writing class. These factors were institutional demands, linguistic needs, enthusiastic and inspiring teachers, engaging activities and tasks, interesting topics, and positive learning atmosphere. The present study suggested that there should be a collaborative negotiation between the teacher and students to create an enjoyable learning atmosphere. This also necessitated teachers to examine learners’ needs, institutional expectations, as well as their characteristics and voices in EFL writing.doi.org/10.24071/ijiet.2017.010104